2020
DOI: 10.21203/rs.3.rs-20260/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disability-adjusted Life Years for respiratory syncytial virus in children under 2 years

Abstract: BACKGROUND : Respiratory syncytial virus infection is the leading cause of bronchiolitis in Colombia. There is growing evidence about the impact of Respiratory syncytial virus on society in terms of years of life lost due to this condition. The objective of the present study is to determine the Disability-Adjusted Life Years for respiratory syncytial virus in children under 2 years in Colombia METHODS : Data from the national epidemiological surveillance system were used to estimate DALYs, calculated from the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Our study are in line with this conclusion being the rst economic evaluation published to this respect. The evaluation of the impact of drug with new indications represent a key issue in health policy development Previous publications have shown that bronchiolitis has a relevant impact on healthcare resources consumption and related expenditures, especially in severe cases, and any intervention that reduces the burden of disease and costs is highly appropriate to any health system (3,4,9,17). Surfactant is the therapy with the highest level of expectations due to a positive effect in PICU length of stay, but still a few evidence in endpoints such as mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study are in line with this conclusion being the rst economic evaluation published to this respect. The evaluation of the impact of drug with new indications represent a key issue in health policy development Previous publications have shown that bronchiolitis has a relevant impact on healthcare resources consumption and related expenditures, especially in severe cases, and any intervention that reduces the burden of disease and costs is highly appropriate to any health system (3,4,9,17). Surfactant is the therapy with the highest level of expectations due to a positive effect in PICU length of stay, but still a few evidence in endpoints such as mortality.…”
Section: Discussionmentioning
confidence: 99%